STRATEGIC TIME MANAGEMENT: YOUR GUIDE TO EFFECTIVE MARKETING TIMING - Jonathan, Elizabeth R. (International Journal of Allied Research in Marketing and Management (IJARMM), 2023)
This study delves into the overlooked yet pivotal role of calendars and calendar timing in marketing strategies. Despite their significance in influencing the outcomes of marketing initiatives, the exploration of these dimensions remains scant in the marketing literature. Charles L. Martin, a distinguished authority in marketing and creator of "calendar-led marketing" (CLM) and "calendar-led buyer behavior" (CLBB), underscores the criticality of temporal factors in shaping consumer behaviors. This paper sheds light on Martin's pioneering insights, which advocate elevating the status of "periodicity" to a paramount position within the marketing mix, alongside conventional elements like product, price, promotion, and place. Martin's discourse emphasizes that the efficacy of the established four P's of marketing hinges on the strategic implementation of "when" these actions occur. By analyzing a compendium of Martin's works, encompassing scholarly articles, books, presentations, and videos, this study underscores the necessity of integrating calendar-oriented considerations into marketing paradigms. This research underscores the need for a paradigm shift in the understanding of temporality and highlights the pivotal role it plays in the success of marketing endeavors.